2009
DOI: 10.1111/j.1582-4934.2009.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated cargo internalized by fusogenic liposomes partially overlaps the endoplasmic reticulum

Abstract: Few endocytosed ligands, including bacterial toxins and simian virus 40 (SV40) have been shown to reach the endoplasmic reticulum (ER) in mammalian cells. Using calcein and fluorescently labelled lactoferrin encapsulated in fusogenic liposomes we found that the cargo uses a microtubule-based pathway with ER delivery. Endocytic uptake of the lipid vesicles was cholesterol dependent in all cell lines tested, including the caveolin-1-deficient human hepatoma 7 cell line. The ligand was transported in non-caveosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In this regard, several intracellular pattern recognition receptors have been identified to date, including ER‐localized proteins like Toll‐like receptor 9 [43]. In addition, the ER itself has been proposed to play a role in processes such as endocytosis [44], cross‐presentation [45], autophagy [46] as well as in the life cycle of several intracellular pathogens [47–49], which all strongly supports the need for ER resident pattern recognition receptors, for which CLEC‐1 may be an interesting candidate. Our attempts to identifiy a ligand for CLEC‐1 included binding experiments using soluble receptors and endothelial cells overexpressing CLEC‐1 as well as experiments scoring activation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several intracellular pattern recognition receptors have been identified to date, including ER‐localized proteins like Toll‐like receptor 9 [43]. In addition, the ER itself has been proposed to play a role in processes such as endocytosis [44], cross‐presentation [45], autophagy [46] as well as in the life cycle of several intracellular pathogens [47–49], which all strongly supports the need for ER resident pattern recognition receptors, for which CLEC‐1 may be an interesting candidate. Our attempts to identifiy a ligand for CLEC‐1 included binding experiments using soluble receptors and endothelial cells overexpressing CLEC‐1 as well as experiments scoring activation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because NP generally cannot directly cross the endosomal membrane, strategies are to use agents to induce fusion between NP and endosomal membrane, in order to disrupt the membrane and promote the NP release from endosomes to cytosol. These processes also promote a microtubule-driven pathway that enables NP to escape from the early endosomes to enter the trans-Golgi network, Golgi apparatus, endoplasmic reticulum (ER), and cytosol, and thereby bypass the lysosomes [132] (Fig. 6).…”
Section: Np Cellular and Subcellular Compartments Targetingmentioning
confidence: 99%
“…It has been reported that the molecular mechanism of the antiproliferative effect of Lf in Jurkat leukemia T cells is mediated through the modulation of the JNKassociated Bcl-2 signaling pathway (Lee et al 2009). In the case of drugs included into liposomes, the intracellular delivery of the content is a complex process, which depends upon the surface charge and size of liposomes, and the type of cells (Trif et al 2001;Mustata et al 2009). Generally, cellular uptake of liposomes is mediated by their absorbtion on the cell surface and subsequent endocytosis.…”
Section: Resultsmentioning
confidence: 99%